A teologia da missão integral e a ciberteologia: desafios e oportunidades para a evangelização dos nativos digitais. - Santos, Andre Guimel Carvalho (2019)
The world faces great transformations in a speed that may cause astonishment, but above all, it must be an appeal to the mission and a task for Theology as it was always placed in challenging historical contexts. In order to respond to the challenges of the mission in the 1970s, the Theology of Integral Mission (IMT) emerged. In that historical moment of contextual theologies, it was necessary to turn to the Latin American reality and within a vision of the human being in its entirety, in order to respond to the demands of the mission in the continent. René Padilla was one of the most relevant theologians in the elaboration of this theology and our speaker . In recent years, however, the context has changed radically, interconnecting the world, thanks in particular to cybernetics: the world has become a global village and speaking the digital language. In the present context, therefore, it is unthinkable to live without these possibilities of communication and outside the network environment. In the desire to contribute to the work of the TMI in cyberspace, the present work investigated several works that deal with TMI, cyberspace and cybertheology, seeking to take the perspective of the digital natives. On the other hand, we approach the theme of cyberspace, especially with the contributions of Pierre Lévy and the studies of cybertheology. We basically support Antônio Spadaro and Moises Sbardelloto. Throughout the research, some questions emerged that guided the course: What is the relevance of the IMT to the new context? Is the IMT capable of seeing cyberspace as a place of mission? Who are the main inhabitants of cyberspace? How to relate TMI, cyberspace and digital natives? Finally, there is a fundamental question: to what extent can cyberspace be considered a true theological place? In any case, the new cybernetic context brought with it great challenges to mission and theology, but certainly also new opportunities, if we were to take on the risky and indispensable task of reinterpreting Christianity here and now.